Early Life Exposure, Lifestyle, and Comorbidity as Risk Factors for Microscopic Colitis: A Case–Control Study. Issue 6 (June 2017) - Verhaegh, Bas P. M.; Pierik, Marieke J.; Goudkade, Danny; Cuijpers, Yvette S. M. T.; Masclee, Ad A. M.; Jonkers, Daisy M. A. E.
Abstract : Background: The pathophysiology of microscopic colitis (MC) is not fully understood. A dysregulation of the adaptive immune response has been hypothesized, of which the maturation and function is imprinted in early life. Various other factors (e.g., hormonal factors) have also been found to be associated, sometimes, with minimal or conflicting evidence. The aims of this study were to evaluate whether an exposure to (microbial) agents in early life might be protective for MC development and to assess the role of several less well-established risk factors in one study. Methods: A case–control study was conducted including MC cases diagnosed in the Southern part of the Netherlands between 2000 and 2012. Cases were matched to non-MC controls from the same area, based on gender and year of birth, and assigned the same index date. All subjects filled out the same study questionnaire on various risk factors. Results: In total, 171 MC cases and 361 controls were included. In the multivariable logistic regression analysis, current smoking (odds ratio 6.23, 95% confidence interval, 3.10–12.49), arthrosis, and a cardiac disorder were associated with MC. No association was observed, for example, factors related to early life exposure to microbial antigens, passive smoking, rheumatoid arthritis, celiac disease, or hormonal factors. Conclusions: Early life exposure to microbial antigens and increased hormonal exposure were not found to be protective for MC. Current smoking seems to be an incontestable risk factor for MC. Therefore, exposure to environmental risk factors later may be of relevance in MC pathogenesis and warrants further investigation. Abstract : Article first published online 2 May 2017.Supplemental Digital Content is Available in the Text.